Medical students as research participants: Student experiences, questionnaire response rates and preferred modes - G Joubert; W J Steinberg; L J van de Merwe (South African Medical Association, 2022)
Background. Research projects frequently include students, a potentially vulnerable population, as participants. Objectives. To determine University of the Free State (UFS) medical students' experiences as research participants. Response rates to and preferences for hard copy and electronic questionnaires were also investigated. Methods. All 804 UFS undergraduate medical students in 2020 were approached to participate in this cross-sectional survey. Fourth- and fifth-year students and one-half of the third-year class were approached in person to complete anonymous hard copy questionnaires in a class setting. First- and second-year students and the other half of the third-year class were contacted electronically to complete anonymous electronic questionnaires. Results. Response rates to hard copy questionnaires were at least ~45% of the entire year group (and >70% of those to whom the questionnaire was distributed in class) compared with approximately a third of those contacted electronically. Students who responded to electronic questionnaires preferred electronic completion, whereas those who responded to hard copy questionnaires preferred the hard copy format, except fifth-year students. The majority of students (except those in their first year) had previously been approached to participate in research projects. Between a fifth and a third of all year groups indicated that they had refused participation at least once. More than a third of fifth-year students experienced insufficient time to decide on participation. Up to a quarter of third- to fifth-year groups had felt pressurised to participate. Conclusion. Hard copy questionnaires in class, the preferred data collection method for many students, produced better response rates but placed potential pressure on students to participate.